GROWTH VARIATION OF SEVERAL POPULATION SOURCES OF Alstonia scholaris (L.) R. Br AT THREE YEARS OLD IN GUNUNG KIDUL - Mashudi Mashudi (Pusbindiklat - LIPI, 2017)
Alstonia scholaris (L.) R. Br is a local species with a broad distribution and has a fairly high economic value. This study was aimed to determine the growth variation of Alstonia scholaris (L.) R. Br from several population sources at three years old in Gunung Kidul, Yogyakarta. The experimental design used was randomized complete block design (RCBD) with two factors, namely the population sources (Lombok, Jayapura, Solok, Timor, and Bali) and parent trees (48 parent trees). In this study parent trees nested in the population sources. Each parent trees planted four trees per plot, four replicates (blocks) with a spacing of 4 x 2 m. Results of variance analysis showed that the population sources significantly influenced by survival rates, the height of growth and stem diameter, and then parent trees affected considerably to the height of growth and stem diameter. The best survival rates were occupied by the Lombok population (93.32%), Bali population (91.96%), and Timor population (89.06%). The best height of growth was occupied by Lombok population (3.04 m) and Bali population (2.88 m), and for stem diameter was Lombok population (5.92 cm). There were seven best parent trees in the height of growth in a range between 3.25 to 3.72 m and 19 best parent trees in the growth of stem diameter ranging from 5.82 to 7.28 cm.